A novel biological role for nsLTP2 from Oriza sativa: Potential incorporation with anticancer agents, nucleosides and their analogues. (October 2015) - Tousheh, Mojtaba; Darvishi, Fatemeh Zahra; Miroliaei, Mehran
Graphical abstract: Highlights: Nonspecific lipid transfer protein (nsLTP2) binds with nucleosides and anticancer drugs. Hydrophobicity of the active site plays prominent role in this regard. Purine analogues drugs presented higher affinity than pyrimidine counterparts. Binding affinity is influenced by the modifications occurring in the base and sugar moiety of the ligands. Abstract: Development of a protein-based drug delivery system has major impact on the efficacy and bioavailability of unstable and water insoluble drugs. In the present study, the binding modes of a nonspecific lipid transfer protein (nsLTP2) from Oryza sativa with various nucleosides and analogous molecules were identified. The 3-D structure of the protein was designed and validated using modeler 9.13, Molegro virtual docker and procheck tool, respectively. The binding affinity and strength of interactions, key contributing residues and specificity toward the substrates were accomplished by computational docking and model prediction. The protein presented high affinity to acyclovir and vidarabine as purine-analogous drugs. Binding affinity is influenced by the core template and functional groups of the ligands which are structurally different cause the variation of interaction energies with nsLTP2. Nonetheless, all the evaluated analogous drugs occupy the proximity space at the nsLTP active site with high similarity in their binding modes. Our findings hold great promise for the future applications of nsLTPs in various aspects of pharmaceutical science and molecular biology.